Reconstructing Gender Relations for Family Resilience in Minangkabau: Integrating Islamic Law and Customary Law - Fakhyadi, Defel; Samsudin, Muhammad Adib; Dasrianto, Vito; Danil, Muhammad; Wahyudi, Ade Arga (Al-Ahkam, 2025)
Women are social beings who hold a high position in continuing the kinship system, preserving the existence of inheritance, and being responsible for forming family ethics and morals. This study aims to reconstruct the legal perspective on gender relations by integrating Islamic law with the Minangkabau cultural customs to strengthen family resilience. This research uses a qualitative approach based on relevant documents from primary and secondary sources, including interviews, documentation, books, and articles. The collected data is analyzed using content analysis methods with phenomenological, feminist, and sociological approaches. The findings of this study indicate that the Minangkabau community views women as charismatic and respected figures. Bundo kanduang protects her kin, preserves the ancestral heritage, and maintains the kinship system to ensure the continuity of the family within the matrilineal kinship system. This research contributes to the discourse on Islamic law and gender by showing how the matrilineal society of Minangkabau aligns with Islamic principles and challenges conventional patriarchal interpretations that are not in line with Islamic values.